Management of Myocardial Reperfusion Injury - Kaski, Juan Carlos; Hausenloy, Derek J.; Gersh, Bernard John; Yellon, Derek M. (Springer London : Imprint: Springer, 2012)
Much has been written about myocardial reperfusion injury and the controversies surrounding its existence and clinical relevance in the past 20 to 30 years. Unfortunately, however, there is little published information that integrates research findings with the practical aspects of its management and this has hindered the analysis of the clinical impact of the condition and its management. The pathophysiology and molecular mechanisms of myocardial reperfusion injury are complex, while individual diagnostic techniques have been proposed but without a proper assessment of the relative values of these methods.  The management of this condition has also been problematic, as therapeutic strategies that demonstrate prevention of myocardial reperfusion injury in experimental models have not translated into beneficial treatment strategies for patients. Management of Myocardial Reperfusion Injury brings together leading cardiovascular researchers and cardiologists to provide a comprehensive and critical review of the issues.  Existing and novel therapeutic strategies for preventing myocardial reperfusion injury are discussed in depth, which will result in this being a vital reference for cardiologists and all healthcare professionals with an interest in the pathogenesis and management of myocardial damage. Cardiologists in training will find this monographic work to be an invaluable formative tool.  This book will hopefully assist in further reducing the morbidity and mortality resulting from acute myocardial infarction.